1991
DOI: 10.1073/pnas.88.14.6219
|View full text |Cite
|
Sign up to set email alerts
|

A myogenic factor from sea urchin embryos capable of programming muscle differentiation in mammalian cells.

Abstract: Using the basic helixloop-helix domain of the myogenic factor myogenin as a probe, we identified a clone from a sea urchin cDNA library with considerable sequence similarity to the vertebrate myogenic factors. This cDNA, sea urchin myogenic factor 1 (SUM-1), transactivated a muscle creatine kinase-chloramphenicol acetyltransferase reporter gene in 1OTI/2 fibroblasts to a level comparable to that of the vertebrate myogenic factors. In addition, bacterially expressed fl-galactosidase-SUM-1 fusion protein interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…This is not the first reported instance of a non-mammalian myogenic factor acting in the 10T1/2 cell line. Venuti et al (1991) isolated a sea urchin analogue of the vertebrate myogenic factors called SUM-1. Transfection of EMSV SUM-1 can convert 10T1/2 cells, and irans-activate muscle-specific reporter gene expression, as efficiently as EMSV mouse MyoD.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the first reported instance of a non-mammalian myogenic factor acting in the 10T1/2 cell line. Venuti et al (1991) isolated a sea urchin analogue of the vertebrate myogenic factors called SUM-1. Transfection of EMSV SUM-1 can convert 10T1/2 cells, and irans-activate muscle-specific reporter gene expression, as efficiently as EMSV mouse MyoD.…”
Section: Discussionmentioning
confidence: 99%
“…In multipotential 10T1/2 cells, transfection experiments have shown that forced expression of these exogenous myogenic factors is sufficient to drive them down the muscle differentiation pathway suggesting their functions in myogenic lineage determination [1][2][3][4][5]. In contrast to vertebrates whose genome encodes multiple members of the MyoD family, invertebrates, including Sea urchin [7], C. elegans [8] and Drosophila [9], appear to contain only a single myogenic factor encoding gene. However, the myogenic factor for Sea urchin and C. elegans activates myogenesis in 10T1/2 cells indicating a highly conserved mechanism for muscle genes activation.…”
mentioning
confidence: 99%
“…Members of this muscle regulatory gene family include MyoD (21), myogenin (25,77), myf5 (9), and MRF4/herculin/myf6 (8,48,61), each of which can activate myogenesis when introduced into a wide range of nonmuscle cell types. Related myogenic factors have also been identified in a variety of vertebrate and invertebrate species (22,30,35,39,44,47,57,65,72). An additional gene, myd, that appears to be structurally unrelated to the MyoD family, has been identified as a genomic clone that can induce myogenesis in 1OT1/2 cells, but it has not yet been characterized at the molecular level (59).…”
mentioning
confidence: 99%